2018
DOI: 10.19126/suje.367429
|View full text |Cite
|
Sign up to set email alerts
|

Thought Errors of the University Students and How Their Expressing Emotions Predict Their Perfectionism Attitude

Abstract: Öz. Bu çalışmanın amacı, üniversite öğrencilerinin duyguları ifade etme ve bilişsel hataları ile mükemmeliyetçilikleri arasındaki yordayıcı ilişkileri incelemektir. Araştırmanın verileri "Frost Çok Boyutlu Mükemmeliyetçilik Ölçeği", "Duyguları İfade Ölçeği" ve ''Bilişsel Hatalar Ölçeği' ile toplanmıştır. Araştırma sonuçlarına göre olumlu duygu ifadesi, aile beklentileri ve yaptığından emin olamama ile pozitif yönde anlamlı ilişki içindeyken düzen boyutuyla ters yönlü anlamlı ilişki içerisindedir. Aynı zamanda … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
1
0
0
1
Order By: Relevance
“…Upon a scrutiny on the related literature, it was seen that the relationship between perfectionism and emotional intelligence had been investigated. In accordance with the studies conducted, a negative relationship was found between perfectionism and emotional intelligence (Çarkıt and Yalçın, 2018;Kaya and Birol, 2018;Kaya and Peker, 2016;Satıcı, 2018;Smith et al, 2014). However, while there was a positive relationship between positive JHTI 5,3 perfectionism and emotional intelligence, there was a negative relationship between negative perfectionism and emotional intelligence (Chan, 2009;Eum and Rice, 2011;Gong et al, 2017;Perrone-McGovern et al, 2017).…”
Section: Literature Review and Development Of Hypotheses By The Resea...supporting
confidence: 75%
“…Upon a scrutiny on the related literature, it was seen that the relationship between perfectionism and emotional intelligence had been investigated. In accordance with the studies conducted, a negative relationship was found between perfectionism and emotional intelligence (Çarkıt and Yalçın, 2018;Kaya and Birol, 2018;Kaya and Peker, 2016;Satıcı, 2018;Smith et al, 2014). However, while there was a positive relationship between positive JHTI 5,3 perfectionism and emotional intelligence, there was a negative relationship between negative perfectionism and emotional intelligence (Chan, 2009;Eum and Rice, 2011;Gong et al, 2017;Perrone-McGovern et al, 2017).…”
Section: Literature Review and Development Of Hypotheses By The Resea...supporting
confidence: 75%
“…Düzen boyutu, standartların belirlenmesi ya da bu standartlara ilişkin performansın nasıl değerlendirildiği ile ilgili olmasa da, bireyin bu standartları karşılama görevini günlük olarak nasıl gerçekleştirdiği ilgilidir (Frost vd., 1990;Frost vd., 1991). Türkiye'de ve yurtdışında yapılan araştırmalarda mükemmeliyetçiliğin bilişsel hatalar ve mantıkdışı inançlarla (Çarkıt, 2016;Çarkıt ve Yalçın, 2018;Dilmaç, Aydoğan, Koruklu ve Deniz, 2009), yalnızlıkla (Arslan, Hamarta, Üre ve Özyeşil, 2010), bipolar bozuklukla (Fletcher vd., 2019) ve yoğun negatif duygularla (Castro, Soares, Pereira ve Macedo, 2017;Dunkley, Zuroff ve Blankstein, 2003;Kobori ve Tanno, 2005;Nejad, Besharat, Haddadi ve Abdolmanafi, 2011) pozitif yönde ilişkili olduğu bulunmuştur. Ayrıca mükemmeliyetçiliğin anksiyete ve depresif semptomları artırdığı (Arslan, Oral ve Karababa, 2018;Levine, Green-Demers, Werner ve Milyavskaya, 2019) ve yaşam doyumunu azalttığı (Karababa, 2018) bulunmuştur.…”
Section: Introductionunclassified